Possible Association Between Vascular Endothelial Growth Factor in Obese and Thin Built Women with PCOS - Abdul Razzaq, Ola Adil; Al-Rubayae, Bushra J. Umran (Academic Journal of Clinicians, 2025)
Polycystic ovary syndrome is a common infertility disorder affecting a significant proportion of the global population. It is the main cause of anovulatory infertility in women and is the most common endocrinopathy affecting reproductive-aged women, with a prevalence of 8–13% depending on the criteria used and population studied. Vascular endothelial growth factor, which is responsible for promoting the proliferation of vascular endothelial cells and regulating vascular permeability, is of great importance in follicular development. This study aimed to evaluate the role of vascular endothelial growth factor level in obese women and thin built women with Polycystic ovary syndrome. This case control study conducted at the Department of Obstetrics and Gynecology at Babylon Maternity and Pediatric Teaching Hospital, during the period from January 2021 to July 2021. Sixty women were enrolled in the study and divided into three groups: Group A: twenty cases as obese women with Polycystic ovary syndrome, group B: twenty cases as thin women with Polycystic ovary syndrome, group C: twenty healthy women as control group Our findings showed a significant difference found between Polycystic ovarian disease groups (thin and obese) regarding Testosterone, and between the groups. Mean value of Vascular endothelial growth factor was (131.14 ± 106.7) in control group while (281.04 ± 143.1) in thin Polycystic ovary syndrome and in obese Polycystic ovary syndrome was (297.46 ± 159.45). In conclusion, a highly significant increase in Vascular endothelial growth factor level in patients with Polycystic ovary syndrome (thin, and obese) than that in healthy subjects (P<0.001), but with no difference found between Polycystic ovary syndrome group (thin+ obese) regarding Vascular endothelial growth factor level